The factors correlated to nurses’ decision activating code blue team in hospital - Ekwantoro Ekwantoro; Kuswantoro Rusca Putra; setyoadi setyoadi (International Journal of Public Health Science (IJPHS), 2021)
The success and hindrances of the blue-code activation were based on nurses’ readiness to request assistance once a patient’s clinical condition decreases. This research aimed to determine the nurses’ hindrance factors in making the blue code activation at hospitals. This research is analytical-observational with a cross-sectional approach. The samples consisted of 93 nurses taken randomly. The data were collected by questionnaire from March until April 2020 at one of the Nganjuk Government Hospitals. The Pearson test result showed a correlation between experience with p-value 0.022, education with a p-value 0.000, cognition with p-value 0.006, and organizational culture with a p-value 0.000 toward decision-making (p-value<0.05). The multiple linear regression multivariate analysis shows an Exp. value (B) of education is 0.292, experience with a value 0.178, cognition with a value 0.194, and cultural organization with a score of 0.425. Thus, it could be concluded that the organizational culture was the most dominant factor of the nurses’ decision making. The hindrances and success of the nurses’ decision-making are based on the nurses’ characteristics, such as cognition, communication skill, and collaboration skill. The support from the leader of an organization would influence nurses’ confidence dealing with patients’ health.